Steering graphene quantum dots in living cells: lighting up the nucleolus. Issue 4 (7th January 2016) - Wang, Xiaojuan; Wang, Yanan; He, Hua; Chen, Xin; Sun, Xing; Sun, Yawei; Zhou, Guangjun; Xu, Hai; Huang, Fang
Abstract : A novel graphene quantum dot capable of lighting up the nucleoli of living cells has been developed. Abstract : The nucleolus is an important subnuclear structure and there are very few dyes available in the market for nucleolar imaging. Subcellular organelles delivery presents a common stumbling block for many nanomaterial-based applications, including intracellular structure fluorescence staining. We now introduce a novel luminescent graphene quantum dot (nGQD), which is able to selectively light up the nucleoli of living cells, to address these challenges. Investigations on subcellular localization of different GQDs have demonstrated that the positively charged surface and the ultra-small size are the key parameters for nucleoli-rich distribution of nanomaterials, which is of importance for transferring this strategy to other nanoparticles. The novel nGQD has great potential to be applied as a nucleolar stain or an efficient gene/drug carrier.